FIELDS OF ANIMATION AND MULTIPLICATION IN UZBEKISTAN: LAST AND TODAY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article depicts in detail the current positive developments in the fields of animation and multiplication, as well as the existing mistakes and shortcomings. Emphasis is placed on the fact that these areas, which are new to today's society, are emerging as an active, influential, dynamic tool in the penetration of human psychology. The role of the sound director in the development of this system is also discussed. Most importantly, in recent years, many examples of creative work created in the field of Uzbek animation and multiplication have been presented and analyzed in detail. A number of proposals and comments were made on the adequate implementation and development of these areas in Uzbekistan, and the necessary conclusions were made.